Relativistic and QED Corrections for the Beryllium Atom - Pachucki, Krzysztof; Komasa, Jacek (American Physical Society, 2004)
Complete relativistic and quantum electrodynamics corrections of order α2 Ry and α3 Ry are calculated for the ground state of the beryllium atom and its positive ion. A basis set of correlated Gaussian functions is used, with exponents optimized against nonrelativistic binding energies. The results for Bethe logarithms lnk0(Be)=5.750 34(3) and lnk0(Be+)=5.751 67(3) demonstrate the availability of high precision theoretical predictions for energy levels of the beryllium atom and light ions. Our recommended value of the ionization potential 75 192.514(80)   cm-1 agrees with equally accurate available experimental values.
Keywords: beryllium atom; relativistic corrections; quantum electrodynamics corrections; Bethe logarithms; Ionization potential; Correlated Gaussian functions